Carbon Emission Reduction—Carbon Tax, Carbon Trading, and Carbon Offset - Wen-Hsien Tsai (Energies, 2020)
The Paris Agreement was signed by 195 nations in December 2015 to strengthen the global response to the threat of climate change following the 1992 United Nations Framework Convention on Climate Change (UNFCC) and the 1997 Kyoto Protocol [...]